THE EFFECT PQ4R STRATEGY AND READING MOTIVATION FOR STUDENTS READING COMPREHENSION - Prima Rahmadia; Sitti Fatimah (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
The purposes of this research are to find out whether (1) significant effect on students reading comprehension (2) PQ4R strategy give better effect in reading comprehension of students with motivation (3) interaction between PQ4R strategy and students reading motivation toward students’ reading comprehension. This type of research is experimental research with a 2x3 factorial design. The sample in this study students of class IX SMA Muhammadiyah 3 Padang was the IX IPS1 as the experimental class using the PQ4R and the IX IPS3 class as the control class using the conventional. The instruments is the Reading Comprehension Test and the Questionnaire of Reading Motivation. The prerequisite test includes the normality test using the Lilliefors method and the homogeneity test using the Bartlett method. It can be concluded that the sample comes from a population that is normally distributed and has homogeneous variance. Hypothesis testing uses two-way analysis of variance with different cells. The results: (1) there is an effect reading comprehension of students who are given PQ4R and conventional model. (2) reading comprehension of students who have low, medium and high learning motivation have the same. (3) There is interaction between the learning model and reading motivation.